Blockchain Technologies and Remittances: From Financial Inclusion to Correspondent Banking - Rella, Ludovico (Frontiers in Blockchain, 2019)
Since their emergence, blockchain technologies have shown potential for financial inclusion and the formalization of remittances. Recently, regulators and practitioners have studied the capabilities of blockchain technologies to streamline and, potentially, replace the infrastructure underpinning cross-border payments and remittances, i.e., correspondent banking. Correspondent Banking Relationships, also called “Nostro-Vostro accounts,” are continuous bilateral arrangements that enable banks to provide services in countries where they do not directly operate. After the Global Financial Crisis, this infrastructure has undergone “de-risking,” i.e., a reduction of correspondent accounts and their concentration in fewer financial institutions, with especially detrimental effects on costs and speed of retail cross-border remittances. The existing literature has mostly focused on the point of sale of remittances, often overlooking correspondent banking. This paper, in contrast, connects remittances, blockchain technologies, and correspondent banking with the growing interest of critical social science in the significance of payment infrastructures for the constitution and configuration of money, finance, and markets. By unpacking the critical case of Ripple, this paper shows that blockchain applications to remittances focus on profits, risks, costs, interoperability, “trapped liquidity,” and “idle capital” in correspondent banking accounts, rather than on financial inclusion per se. In so doing, this paper contributes to critical social studies literature on the formalization of remittances, understood as the transformation of remittances into a market frontier. Blockchain applications are shown to foster, rather than resist, remittances formalization, and they are presently being incorporated into existing infrastructures, business models, and regulatory structures. Rather than representing radically alternative monetary systems, blockchain technologies are the latest iteration of technologies heralding frictionless capitalism. Lastly, this paper shows the tensions and ambiguities inherent to interoperability and formalization. Blockchain technologies are dynamic in a way that problematizes dichotomies such formal-informal and mainstream-alternative. Hence, rather than providing a quantitative assessment of the impact of blockchain technologies, this paper investigates the ambiguities and tensions in the political economy and imaginaries inscribed in the materiality and design of blockchain-enabled payment systems.